Systematic review to evaluate algorithms for REBOA use in trauma and identify a consensus for patient selection - Jonathan Nguyen; Andrew Beckett; Chance Spalding; Ernest E Moore; Bradley M Dennis; Jonathan James Morrison; John Hunt; Elizabeth Benjamin; Rishi Kundi; Juan Duchesne; Amelia Walling Maiga; Ryan Lawless; et al. (Trauma Surgery & Acute Care Open)
Background Patient selection for resuscitative endovascular balloon occlusion of the aorta (REBOA) has evolved during the last decade. A recent multicenter collaboration to implement the newest generation REBOA balloon catheter identified variability in patient selection criteria. The aims of this systematic review were to compare recent REBOA patient selection guidelines and to identify current areas of consensus and variability.Methods In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we conducted a systematic review of clinical practice guidelines for REBOA patient selection in trauma. Published algorithms from 2015 to 2022 and institutional guidelines from a seven-center REBOA collaboration were compiled and synthesized.Results Ten published algorithms and seven institutional guidelines on REBOA patient selection were included. Broad consensus exists on REBOA deployment for blunt and penetrating trauma patients with non-compressible torso hemorrhage refractory to blood product resuscitation. Algorithms diverge on precise systolic blood pressure triggers for early common femoral artery access and REBOA deployment, as well as the use of REBOA for traumatic arrest and chest or extremity hemorrhage control.Conclusion Although our convenience sample of institutional guidelines likely underestimates patient selection variability, broad consensus exists in the published literature regarding REBOA deployment for blunt and penetrating trauma patients with hypotension not responsive to resuscitation. Several areas of patient selection variability reflect individual practice environments.Level of evidence Level 5, systematic review.